Efektivitas Edukasi Pembuatan Jus Labu Siam Terhadap Pengetahuan Untuk Mencegah Hipertensi Di Dusun Maccini Ayo 2024 - Surahmawati, Surahmawati; Hasanah, Andi Nida'ul; Aisyah, Nabila Salsabilah; Azmi, Shinta Ulul (Universitas Negeri Gorontalo, 2024)
THE EFFECTIVENESS OF EDUCATION ON MAKING CHAYOTE JUICE ON KNOWLEDGE TO PREVENT HYPERTENSION IN MACCINI AYO HAMLET 2024. Hypertension is a disease that occurs due to too high blood pressure, namely when systolic blood pressure 140 mmHg and / or diastolic blood pressure 90 mmHg. Based on the results of blood pressure measurements taken in Maccini Ayo Hamlet, Bontomanai Village, Rumbia Sub-District, Jeneponto Regency, it was found that as many as 80% of Maccini Ayo hamlet residents had high blood pressure. One of the causes of high cases of hypertension is due to the lack of public understanding of hypertension. The purpose of this study was to assess the effectiveness of education and training on making chayote juice as a hypertension-lowering food on increasing the knowledge of the people of Maccini Ayo Hamlet, Bontomanai Village, Rumbia District, Jeneponto Regency. The research method used is quantitative by giving Pre Test and Post Test. The respondents in this study were residents of Maccini Ayo Hamlet with a total of 35 respondents. This research was conducted on October 03-17, 2024. The data analysis used in this study was the Wilcoxon test. Based on the results of research conducted in Maccini Ayo Hamlet, there was an increase in the average value of knowledge before education was 45.43 and after education was given it increased to 82.29 with a p-value of 0.000 0.05, so it was concluded that the education provided was effective for increasing the knowledge of the Maccini Ayo Hamlet Community regarding the prevention of hypertension with chayote juice.